Les femmes sans mari des classes populaires, des prostituées ? Arbitraire administratif et résistances des femmes (Bucarest, 1850-1870) - Lucian Dumitru Dărămuș (Genre & Histoire)
Beginning with the new Civil Code of 1864, Rumanian women moved from a position of legal incapacity, defined at the beginning of the nineteenth century, to one of absolute dependency on their husbands. This placed them within an ideological construct that circumscribed all female social legitimacy to wedlock. Henceforth, women without husbands who remained outside any male legal control appeared to be potentially immoral or a source of danger for all of society in the eyes of public authorities. As a result, they were registered as public women and subject to prostitution control policies. Through an examination of the strategies of some of these women to escape punitive measures reserved for the so-called immoral women, this article seeks to identify the forms of resistance to and subversion of the marital norm. It shows that a woman without a husband is not a woman without men: relatives, partners, lovers and male neighbors, as well as work itself, offered the means to escape a sexual regulation that sought to impose, through the prostitution system and the status of public women, a form of social illegitimacy to women outside of marriage.